 # Bellwork 3/ (Solve) 1.) x2 + 6x - 7 = 0 2.) x2 + x - 12 = 0

## Presentation on theme: "Bellwork 3/ (Solve) 1.) x2 + 6x - 7 = 0 2.) x2 + x - 12 = 0"— Presentation transcript:

Bellwork 3/ (Solve) 1.) x2 + 6x - 7 = 0 2.) x2 + x - 12 = 0 3.) x2 + 6x + 5 = 0 4.) 2x2 + 7x + 6 = 0

1.) x2 + 6x - 7 = 0 (x -1)(x + 7) = 0 x - 1 = 0 & x + 7 = 0
Bellwork 3/ (Solve) 1.) x2 + 6x - 7 = 0 (x -1)(x + 7) = 0 x - 1 = & x + 7 = 0 x = & x = -7

2.) x2 + x - 12 = 0 (x - 3)(x + 4) = 0 x - 3 = 0 & x + 4 = 0
Bellwork 3/ (Solve) 2.) x2 + x - 12 = 0 (x - 3)(x + 4) = 0 x - 3 = 0 & x + 4 = 0 x = & x = -4

3.) x2 + 6x + 5 = 0 (x + 1)(x + 5) = 0 x + 1 = 0 & x + 5 = 0
Bellwork 3/ (Solve) 3.) x2 + 6x + 5 = 0 (x + 1)(x + 5) = 0 x + 1 = 0 & x + 5 = 0 x = & x = -5

Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 Since you can’t factor out the 2 of the 2x2, you are stuck with it and you must try different factors.

These are all the different factors.
Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 These are all the different factors. Which one works? Try (2x +2)(x + 3) Try (2x +1)(x + 6) Try (2x +6)(x + 1) Try (2x +3)(x + 2)

4.) 2x2 + 7x + 6 = 0 Try (2x +2)(x + 3) x2 + 6x + 2x + 6 x2 + 8x + 6
Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 Try (2x +2)(x + 3) x2 + 6x + 2x + 6 x2 + 8x + 6 Doesn’t work

4.) 2x2 + 7x + 6 = 0 Try (2x +1)(x + 6) x2 + 12x + 1x + 6 x2 + 13x + 6
Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 Try (2x +1)(x + 6) x2 + 12x + 1x + 6 x2 + 13x + 6 Doesn’t work

4.) 2x2 + 7x + 6 = 0 Try (2x +6)(x + 1) x2 + 2x + 6x + 6 x2 + 8x + 6
Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 Try (2x +6)(x + 1) x2 + 2x + 6x + 6 x2 + 8x + 6 Doesn’t work

4.) 2x2 + 7x + 6 = 0 Try (2x +3)(x + 2) x2 + 4x + 3x + 6 x2 + 7x + 6
Bellwork 3/ (Solve) 4.) 2x2 + 7x + 6 = 0 Try (2x +3)(x + 2) x2 + 4x + 3x + 6 x2 + 7x + 6 Ya ba da ba doo

Quiz 3/30 Do 1- 6 of the Quiz.

Try These (Solve) 1.) 3x2 + 11x - 4 = 0 2.) 2x2 +5x + 3 = 0 Your Turn

What are all the factors that you can use for -4? 1• -4, -1• 4, 2• -2
Try These (Solve) 1.) 3x2 + 11x - 4 = 0 What are all the factors that you can use for -4? 1• -4, -1• 4, 2• -2

1.) 3x2 + 11x - 4 = 0 ( )( ) = 0 step 1 (3x )(x ) = 0 step 2
Try These (Solve) 1.) 3x2 + 11x - 4 = 0 ( )( ) = 0 step 1 (3x )(x ) = 0 step 2 (3x - 1)(x + 4) = 0 factor

1.) 3x2 + 11x - 4 = 0 (3x - 1)(x + 4) = 0 3x - 1 = 0 & x + 4 = 0
Try These (Solve) 1.) 3x2 + 11x - 4 = 0 (3x - 1)(x + 4) = 0 3x - 1 = 0 & x + 4 = 0 3x = 1 & x = -4 x = 1/3

2.) 2x2 +5x + 3 = 0 (2x )(x ) = 0 (2x + 3)(x + 1) = 0 The Check:
Try These (Solve) 2.) 2x2 +5x + 3 = 0 (2x )(x ) = 0 (2x + 3)(x + 1) = 0 The Check: 2x2 +2x + 3x + 3 = 0

2.) 2x2 +5x + 3 = 0 (2x + 3)(x + 1) = 0 2x + 3 = 0 & x + 1 = 0
Try These (Solve) 2.) 2x2 +5x + 3 = 0 (2x + 3)(x + 1) = 0 2x + 3 = 0 & x + 1 = 0 2x = & x = -1 x = -3/2

Special Problems (Solve)
1.) x2 - 4 = 0 2.) 4x2 - 9 = 0 3.) x = 0 4.) 9x = 0 The difference of 2 perfect squares

Special Problems (Solve)
1.) x2 - 4 = 0 (x - 2)(x + 2) = 0 x - 2 = 0 & x + 2 = 0 x = & x = -2

Special Problems (Solve)
2.) 4x2 - 9 = 0 (2x - 3)(2x + 3) = 0 2x - 3 = 0 & 2x + 3 = 0 2x = & 2x = -3 x = 3/2 & x = -3/2

Special Problems (Solve)
3.) x = 0 4.) 9x = 0 Your Turn

Special Problems (Solve)
3.) x = 0 (x - 5)(x + 5) = 0 x - 5 = 0 & x + 5 = 0 x = & x = -5

Special Problems (Solve)
4.) 9x = 0 (3x - 10)(3x + 10) = 0 3x - 10 = 0 & 3x + 10 = 0 3x = & 3x = -10 x = 10/3 & x = -10/3

Classwork 3/30 Do 5 & 6 of the Quiz. Homework: Chapter 10 Review

Similar presentations